Gastronomy Tourism dalam Perspektif Pemasaran Destinasi: Systematic Literature Review and Bibliometric Mapping Using VOSviewer - Paulina Aruan; Nanang Suryadi (Cv. Syntax Corporation Indonesia, 2025)
Gastronomic tourism has grown rapidly over the past decade and has become a strategic element in the development of tourism destinations in various countries, including Indonesia. This study aims to map scientific developments, conceptual patterns, and research gaps related to gastronomic tourism through a Systematic Literature Review (SLR) approach combined with bibliometric analysis using VOSviewer. A total of 327 Scopus-indexed articles from 2019–2025 were evaluated, and 71 articles met the inclusion criteria for in-depth analysis. The bibliometric visualization results identified five main research clusters: culinary authenticity and quality; tourist experience–satisfaction–loyalty; cultural heritage and local cuisine; supply chain sustainability; and destination marketing, including digital and social media influence. The thematic synthesis reinforces the dominant model of tourist behavior in the literature, namely that authenticity is a key determinant in shaping gastronomic experiences, which then influences satisfaction, and ultimately determines tourist loyalty to the destination, with strong support from heritage, sustainability, and digital branding variables. In addition to offering a conceptual map of global and Indonesian gastronomy research, this study identifies 15 research gaps covering issues such as multidimensional authenticity, sensory experiences, circular gastronomy, and digital influences on tourist behavior. This SLR provides theoretical contributions through the development of an integrative theoretical model, as well as practical contributions for tourism stakeholders in designing culinary-based destination strategies that are authentic, sustainable, and globally competitive.